CHARACTERISTICS OF TAEKWONDO PLAYERS' BEHAVIOR IN COMPETITIONS - Nuritdinova Sh. N. (Journal Park Publishing, 2023)
Forming a healthy lifestyle in our society, creating conditions suitable for the population, especially the young generation, to regularly engage in physical education and mass sports, strengthening the confidence of young people in their will, strength and capabilities through sports competitions, courage and patriotism, to the motherland Wide-scale work is being carried out aimed at developing feelings of loyalty, as well as systematic organization of selection of talented athletes from among young people, as well as further development of physical education and mass sports.
Keywords: Psychological preparation, self-assessment, adolescent taekwondo players, behavioral assessment, expert assessment, self-control.